2022
DOI: 10.1039/d2nr02911a
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric-assisted charge carrier separation over Bi2MoO6 nanosheets for photocatalytic dye degradation

Abstract: Low energy conversion efficiency from absorbed photon to catalytic species remains the major obstacle for real application of photocatalysis. In recent years, the introduction of built-in electric field is proved...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The Mo 3d spectrum of BMO displayed two peaks centered at 232.6 and 235.73 eV, which could be assigned to Mo 6+ 3d 5/2 and 3d 3/2 (Figure b) . The Bi 4f spectrum of BMO at 159.27 and 164.58 eV (Figure c) is in agreement with Bi 3+ 4f 7/2 and 4f 5/2 . Notably, the two peaks were determined in Figure d at 459.56 and 465.25 eV, which were assigned to the TS-1 of Ti 4+ 2p 3/2 and 2p 1/2 , respectively .…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The Mo 3d spectrum of BMO displayed two peaks centered at 232.6 and 235.73 eV, which could be assigned to Mo 6+ 3d 5/2 and 3d 3/2 (Figure b) . The Bi 4f spectrum of BMO at 159.27 and 164.58 eV (Figure c) is in agreement with Bi 3+ 4f 7/2 and 4f 5/2 . Notably, the two peaks were determined in Figure d at 459.56 and 465.25 eV, which were assigned to the TS-1 of Ti 4+ 2p 3/2 and 2p 1/2 , respectively .…”
Section: Resultssupporting
confidence: 59%
“…43 The Bi 4f spectrum of BMO at 159.27 and 164.58 eV (Figure 3c) is in agreement with Bi 3+ 4f 7/2 and 4f 5/2 . 44 Notably, the two peaks were determined in Figure 3d at 459.56 and 465.25 eV, which were assigned to the TS-1 of Ti 4+ 2p 3/2 and 2p 1/2 , respectively. 45 However, the Ti 4+ 2p 3/2 peak area of TS-1/BMO was smaller in comparison to TS-1, and the Ti 4+ 2p 1/2 peak area was larger than TS-1, which might be because of the reduction of extra framework Ti species of TS-1.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…The hybridization between O 2p and Bi 6s states at the valence band leads to a narrowed band gap (ranging from 2.4 to 2.7 eV), enabling effective visible light absorption (Figure S1). , Additionally, the IEF within Bi 2 MoO 6 , resulting from the polarization caused by the positive and negative charges of the (Bi 2 O 2 ) 2+ and (MoO 4 ) 2– layers, respectively, facilitates the efficient separation of photogenerated charge carriers. , Extensive investigations with various forms of Bi 2 MoO 6 have been reported for many applications such as the degradation of organic molecules, water oxidation to produce O 2 gas, NO oxidation, CO 2 reduction, amines coupling reaction, Cr­(VI) reduction, and toluene and ethylbenzene oxidation. However, the photocatalytic performance of Bi 2 MoO 6 is currently limited due to poor quantum efficiency, resulting from insufficient separation of photoexcited charge carriers and surface active sites …”
Section: Introductionmentioning
confidence: 99%
“…Also, the polarization intensity can be enhanced through poling treatment, thus providing a more efficient, long-lasting charge separation effect. Hui et al 33 synthesized Bi 2 MoO 6 nanosheets with superior photocatalytic efficiency toward RhB degradation, and was further enhanced by corona poling treatment. 33 Park et al 34 realized H 2 evolution through KNN, and found out that polarized KNN can reach 7.4 times the original catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Hui et al 33 synthesized Bi 2 MoO 6 nanosheets with superior photocatalytic efficiency toward RhB degradation, and was further enhanced by corona poling treatment. 33 Park et al 34 realized H 2 evolution through KNN, and found out that polarized KNN can reach 7.4 times the original catalytic efficiency. 34 These works have proven that polarization can evidently enhance the photocatalytic efficiency of ferroelectrics, and is a promising strategy in future catalyst design.…”
Section: Introductionmentioning
confidence: 99%